PENGARUH STRUKTUR KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, KUALITAS AUDIT, KOMITE AUDIT DAN LEVERAGE TERHADAP MANAJEMEN LABA - Rexy Joseph S. Dimara; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to analyze the impact of managerial ownership, size corporation, auditor quality, audit committe and leverage towards earning management. The independent variables in this research are the structure of managerial ownership, size corporation, auditor quality, audit commite and leverage. Earning management as variable dependent is measured by dicretionary accrual as proxy from earning management.This study uses secondary data with entire population of manufacturing compianies listed in the Indonesian stock Exchange (BEI) in 2013-2015. The method used to determine the sample is using purposive sampling, producing 213 observations for research in three months from 71 sampel corporation . The analytical method used is multiple linear regreesion, regression testing the prior to first tasted the classical assumptions.The result of this study indicate that size corporation and leverage has significant influence to earning management. Auditor quality, audit committe and managerial ownership did not have significant influence to earning management.